Waste, social order, and physical disorder in small-town India - Harriss-White, B (Taylor and Francis, 2019)
India’s waste is growing fast; so is its research, and so is the informal economy in which it is embedded. Here research on a small-town waste economy (WE) is situated in the literature on urban informal waste, making three contributions. First, an analytical grid is placed over this small-town formal-informal waste economy in terms of its circuits of capital in the generation of waste. These comprise factory production, physical and economic distribution, consumption, the production of labour and the reproduction of society. Second, field evidence for this waste economy is used to interrogate the three prevailing approaches to theorising informality, revealing how social and economic segmentation can simultaneously drive all three theorised relationships in a complementary fashion. Third, the municipal government’s fragmented architecture and informal bureaucratic behaviour reveal not only severely compromised management capacities but also the local state’s paradoxical dependence on, and distance from, the informal waste economy.